2019
DOI: 10.1016/j.childyouth.2018.11.049
|View full text |Cite
|
Sign up to set email alerts
|

Understanding support network capacity during the transition from foster care: Youth-identified barriers, facilitators, and enhancement strategies

Abstract: This study explores how foster care experiences can impact support network functionality as young people exit the foster care system. This can be conceptualized as a function of both network member capacity to provide adequate support to address young adult needs, and network stability, which reflects cohesion within and across relationships to facilitate consistent support over time. We conducted support network mapping and semi-structured interviews with youth in foster care aged 16-20 (N=22) and used theore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 60 publications
4
30
0
Order By: Relevance
“…Additionally, youth connect with family members, deepen new face-to-face relationships, and find new friends in a setting where they can control their self-disclosure. Relational connections reduce many risks to youth as the age out of care (Blakeslee & Best, 2019). Self-disclosure via ICTs appears to strengthen online and in-person relationships (Desjarlais, 2020).…”
Section: Connectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, youth connect with family members, deepen new face-to-face relationships, and find new friends in a setting where they can control their self-disclosure. Relational connections reduce many risks to youth as the age out of care (Blakeslee & Best, 2019). Self-disclosure via ICTs appears to strengthen online and in-person relationships (Desjarlais, 2020).…”
Section: Connectionmentioning
confidence: 99%
“…This skill relies on interpersonal experiences. Again, foster youth often lack opportunities for interpersonal social supports (Best & Blakeslee, 2020;Blakeslee & Best, 2019). Youth participants across studies reported that they developed relational skills through the use of ICTs that provided insights into others' experiences and allowed them to reflect more deeply on their own experiences.…”
Section: Caring/compassionmentioning
confidence: 99%
See 1 more Smart Citation
“…Building on prior work (Blakeslee & Best, 2019), this study takes a network approach to understanding strong ties from youth perspectives as well identifying multiple sources of support and meaningful relationships. This approach represents an effort to move beyond prescriptive understandings of relational permanence, such as relationships with a singular supportive and caring adult, parent-like figure, or mentor.…”
Section: Current Studymentioning
confidence: 99%
“…Youth ages 16 through 20 who were in foster care at the time of recruitment were eligible to participate. We employed a purposive approach to sampling and recruitment; recruitment occurred in three phases and yielded a total of 22 participants (see Blakeslee & Best, 2019). First, youth attending a statewide ILP conference focused on post-secondary career preparation and planning, participated in a social support network mapping workshop and self-selected to participate.…”
Section: Recruitmentmentioning
confidence: 99%